Digital Empowerment and Value Guidance: Construction and Empirical Study of an AI-Supported "Three-Dimensional Competence" Cultivation Model for College English - Wang, Yusu (Education Insights, 2026)
The rapid construction and strategic development of the Hainan Free Trade Port urgently require the coordinated advancement of advanced language proficiency, profound cross-cultural literacy, and robust ideological and political awareness among university graduates. Aiming to address the persistent problems currently prevalent in college English teaching—such as weakened value guidance, the overly explicit and rigid integration of ideological and political elements, vague ability assessment metrics, and the largely superficial application of artificial intelligence (AI) technologies—this study proposes an innovative pedagogical framework. Specifically, a comprehensive three-dimensional training model encompassing "language skills, cross-cultural cognition, and ideological and political literacy" is systematically constructed, and an AI-empowered teaching closed loop is meticulously designed to facilitate personalized learning. To validate the effectiveness of this proposed framework, a rigorous empirical study was conducted involving 110 college students over a duration of 16 weeks. The quantitative and qualitative results demonstrated that the experimental group performed significantly better than the control group across multiple dimensions, particularly in terms of terminology accuracy, cross-cultural etiquette adaptability, and the active proportion of ideological and political practice. Furthermore, the students' policy comprehension and value judgment abilities experienced substantial increases of 42.3% and 37.6%, respectively. Ultimately, this research provides robust theoretical foundations and highly actionable practical paths for the cultivation of globally competent international talents and the advancement of AI-empowered ideological and political education in higher education institutions.